Microstructure and mechanical properties of 631 Stainless Steel: Study of Yield Slip and Strain Rate Mechanism with Austempering and Martempering - Chien-Te Huang; Fei-Yi Hung; Jun-Ren Zhao; Ho-Yen Hsieh (Journal of Alloys and Metallurgical Systems, 2023)
The microstructure and mechanical properties of 631 stainless steel, including tensile fracture and impact toughness, were compared in this study between austempering and martempering processes. The experimental results showed that the mechanical properties of 631 stainless steel increased as the temperature of martempering process increased from 520 °C to 720 °C, in contrast to previous literature, which suggested that the optimal tempering temperature was around 500 °C. Furthermore, 631 stainless steel treated with 720 °C austempering has superior tensile strength and impact toughness to traditional martempered 631 stainless steel. This suggests that the austempering process not only conserves energy but also improves the mechanical properties of 631 stainless steel. Furthermore, the precipitation mechanism during the tempering process can reduce the slip of secondary yield in 631 stainless steel. Additionally, the precipitation mechanism during tempering process can alleviate the secondary yield of 631 stainless steel. In both tensile strain rate tests and high-speed impact tests, it was confirmed that austempered 631 stainless steel had potential application in springs due to low strain-induced embrittlement susceptibility. Furthermore, long-term (24 hr) high-temperature tempering treatment showed that 631 stainless steel still maintained reliability and stability in high-temperature environment.